2014
DOI: 10.1111/rec.12164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spoil type on afforestation success and natural vegetative recolonization on a surface coal mine in Appalachia, United States

Abstract: Surface mining has altered a vast land area in the Appalachian Region, threatening highly biodiverse native forest, contributing to habitat fragmentation, and generating severely disturbed sites that are unsuitable for succession to native ecosystems. Although there are many factors that influence species colonization and establishment on these sites, selection of topsoil substitutes suitable for native species is of particular concern. A series of experimental plots was installed in 2005 on a reclaimed mine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 39 publications
(62 reference statements)
9
33
0
1
Order By: Relevance
“…Large portions of the project site exhibited poor drainage and even standing water (which can frequently be the case on these sites [52,53]), suggesting that overall soil moisture conditions may be more favorable for loblolly pine than shortleaf pine. Chemically, soils were favorable across treatments, with pH, particle size distribution, nutrient levels, and CEC similar to those observed on soils favorable for tree growth and survival in another eastern Kentucky study [6]. However, the soils in loblolly pine plots in this study were chemically more favorable than the soils in shortleaf pine plots, with higher total N and exchangeable Mg.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Large portions of the project site exhibited poor drainage and even standing water (which can frequently be the case on these sites [52,53]), suggesting that overall soil moisture conditions may be more favorable for loblolly pine than shortleaf pine. Chemically, soils were favorable across treatments, with pH, particle size distribution, nutrient levels, and CEC similar to those observed on soils favorable for tree growth and survival in another eastern Kentucky study [6]. However, the soils in loblolly pine plots in this study were chemically more favorable than the soils in shortleaf pine plots, with higher total N and exchangeable Mg.…”
Section: Discussionsupporting
confidence: 65%
“…Shortleaf pine survival (42%) was similar to that of planted hardwoods, but lower than that of loblolly pine (85%) (p < 0.05). Survival of shortleaf pine was lower than first-year survival reported by Angel (2008) of mixed hardwoods planted into mixed mine spoils with no vegetative competition in eastern Kentucky (69-98%) [6,45], lower than survival (65-75%) of seedlings planted into spoils seeded with groundcover species [46], and lower than first-year chestnut survival in legacy mined land in eastern Kentucky (72-97%) [9]. However, shortleaf pine survival was similar to survival of seedlings planted into mine spoil seeded with groundcover species (56%) [47], and greater than survival of shagbark hickory (Carya ovata) reported in the same study (24%) [47].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In many surface mining sites, the topsoil soils are completely destroyed by mine exploitation. The related research has indicated that the mine soils composed of crushed overburden can provide a suitable soil substitute when native soil is unavailable for use in mine reclamation practice [69]. The suitable soil substitutes, such as weathered mine spoils, should be selected carefully by analyzing the characteristics of mine spoil.…”
Section: Uncertainties Involved In the Land Suitability Analysis And mentioning
confidence: 99%
“…A constructed minesoil is usually compacted by excessive machine traffic, which results in inadequate physical conditions for plant growth and development (Lunardi Neto et al, 2008;Sheoran et al, 2010;Borůvka et al, 2012;Stumpf et al, 2014;Sena et al, 2015), as well as a decrease in the biodiversity of soil fauna (Oliveira Filho et al, 2014) and carbon losses due to mechanical mixing of soil horizons (A, B, and/or C) during the operations of removal, transport, and placement of the soil (Ussiri and Lal, 2005;Leal et al, 2015). In addition to these impacts, in mine waste piles derived from coal processing (usually enriched in pyrite), the process of soil aggregation and structuring by the root system of cover crops can promote input of oxygen and water and increase the development of acid mine drainage in the reclaimed area (Quiñones et al, 2008;Campaner and Luiz-Silva, 2009;Costa and Zocche, 2009;Inda et al, 2010;Daniels and Zipper, 2010;Moura, 2014) Reclamation of a mined area should return a degraded ecosystem to a non-degraded condition, which may be different from the original environment (Ibama, 2011).…”
Section: Introductionmentioning
confidence: 99%